(untitled) (ASEAN Legal Insights, 2024)
The corporatisation of Malaysia’s water services marks a significant shift in governance and regulation, transitioning from public ownership to corporatised entities operating under the asset-light model. This article explores the legal implications of this transition, focusing on the Water Services Industry Act 2006 (WSIA) and the related legal framework. Through doctrinal legal analysis, this study examines the impact of corporatisation on governance, tariff setting, financial sustainability, and regulatory compliance. The analysis also highlights the federal government’s role in providing financial support, while addressing challenges faced by water operators; particularly the need to balance commercial objectives with public service obligations amidst low tariffs and operational inefficiencies. Insights from Singapore’s water services industry also offer valuable lessons for Malaysia, particularly in relation to governance and public-private partnerships (PPPs) that promote sustainable water management. The findings suggest that while corporatisation presents potential benefits, significant challenges remain in ensuring that regulatory frameworks are equipped to support both efficiency and public service delivery. The study concludes by recommending improvements to Malaysia’s water services governance, informed by lessons from Singapore, and by addressing key regulatory and financial obstacles.